2019
DOI: 10.1590/1981-22562019022.180225
|View full text |Cite
|
Sign up to set email alerts
|

Reach of “VAMOS” program in basic healthcare - organizational barriers and facilitators

Abstract: Objective : To investigate the organizational barriers and facilitators to the reach of the “Active Life Health Improvement Program” (or VAMOS) implemented in two Basic Health Units (BHU) in Santa Catarina, Brazil. Method : An experimental study was carried out, based on the RE-AIM framework (http://www.re-aim.org/). Barriers and facilitators were identified through a focus group, semi-structured interview and content analysis. Results : In terms of reach, of the 297 Basic Health Care (BHC) users from the tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…In our study, the scarcity of health professionals was a significant impacting adoption. Prior research (Borges et al, 2019;Maissiat, Lautert, Pai, & Tavares, 2015) has suggested that turnover of professionals in health teams and exhaustion, overwork, and the high number of work responsibilities are among the reasons UBS professionals fail to adopt interventions. A multiprofessional approach that emphasizes collaborative teams is essential for success in the SUS system in Brazil (Santos, Guerra, Andrade, & Florindo, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the scarcity of health professionals was a significant impacting adoption. Prior research (Borges et al, 2019;Maissiat, Lautert, Pai, & Tavares, 2015) has suggested that turnover of professionals in health teams and exhaustion, overwork, and the high number of work responsibilities are among the reasons UBS professionals fail to adopt interventions. A multiprofessional approach that emphasizes collaborative teams is essential for success in the SUS system in Brazil (Santos, Guerra, Andrade, & Florindo, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…25,26 A health intervention for Brazilian elderly reported a reach of 17.2%. 27 Another study reported that low attendance of clients at nutrition-education and PA sessions was largely due to inadequate attention of trainers or coaches paid to activities of participants. 28 In the current study, some clients stated that the prescribed physical activities were not suitable for their health conditions and they sometimes experienced difficulties in carrying them out.…”
Section: Discussionmentioning
confidence: 99%
“…The reported reach rate of the evaluated program (20.0%) was considered as a low level reach rate. In another study, the reach rate of a health program on Brazilian elderly was reported 17.2% (35). The low reach of existing programs has made the policy makers worried.…”
Section: Overall Contextual Aspects Affecting the Programmentioning
confidence: 99%